Evaluación del cuidado domiciliario a Pacientes con Pie Diabético durante la pandemia por COVID-19. Centro de Salud Indio Guayas. periodo noviembre 2020 - marzo 2021. - Jarrín Escobar, Adriana Estefanía (2021)
Diabetes, a chronic disease that appears due to insulin insufficiency, which due to uncontrolled diabetes becomes the main cause of death worldwide, is the disease with the greatest social and health impact, not only due to its high prevalence but also due to the development of Chronic complications that lead to a diagnosis of diabetic foot, for which an evaluation and home care will allow a lower incidence of this neuropathy, prevention is prioritized in patients, seeking adequate care and treatment, orienting them towards health and inclusion services to the benefits that the MSP provides for the care of patients with diabetic foot ulcers, whose sole objective is to prevent ailments, more injuries or an amputation of their lower limbs. The purpose is to encourage the nursing staff of the "Indio Guayas" Health Unit to make home visits to patients with diabetic foot for better treatment, care and self-care of their injury in search of a treatment and service that improve the quality of life of the patient, so this research work is detailed: Chapter 1: Problem statement, problem formulation, general objective, specific objectives and justification. Chapter 2: Reference framework, research background, theoretical bases, system of variables and operationalization of variables that allows contextualizing the subject. Chapter 3: Research methodology, information gathering technique and data analysis and interpretation. Chapter 4: Achievements and Results that have been obtained based on the objectives set in the research. Chapter 5: Conclusions and recommendations that are reached after the development of the research project.